Perceptions of the Sandwich Generation of Mataram City on the Effect of Financial Literacy, Financial Distress and Income Level on Financial Behavior - Olif Jufita Awlia; Elin Erlina Sasanti (Asian Journal of Management, Entrepreneurship and Social Science, 2025)
This study aims to determine the effect of financial literacy, financial distress and income level on financial behavior based on the perceptions of the sandwich generation in Mataram City. The population in this study is the sandwich generation in Mataram City. This study uses associative research with a quantitative approach in the form of primary data obtained through distributing questionnaires to the sandwich generation and the number of returned questionnaires is 119 respondents. The data analysis tool used is SmartPLS 4.1.0.9. The results showed that financial literacy has a significant effect on the financial behavior of the sandwich generation in Mataram City, meaning that the higher the level of financial literacy of the sandwich generation, the stronger their foundation in facing major challenges in managing finances, especially in the midst of multiple responsibilities. However, financial distress and income level have no effect on the financial behavior of the sandwich generation, meaning that the financial behavior of the sandwich generation in Mataram City is not influenced by the financial difficulties experienced and their income both in the high and low groups does not affect their behavior towards managing their finances.